COMPLEX SUPPORT SYSTEMS FOR THE ACCEPTANCE OF INNOVATIVE DECISIONS IN ENVIRONMENTAL PROTECTION - Teliura, N.; Lomakina О. (Municipal economy of cities. Series: «Economy science», 2023)
Complex systems for substantiation of innovative ecological solutions to reduce man-made impact on the environment were studied. Ways to increase environmental safety on the basis of sustainable development through a well-founded complex selection of innovative solutions are proposed. Ways to increase environmental safety on the basis of sustainable development through a well-founded complex selection of innovative solutions are proposed. Based on the method of analysis of hierarchies (MAI), a methodical approach for determining the priority innovative ecological solutions. The developed approach makes it possible to involve experts in environmental, urban planning, social, and economic direction of municipal management bodies of a specific settlement, industrial, residential, and military facilities. According to the developed approach, criteria formulated as influencing groups of factors. Relevant experts, relying on various types of information on the specific purpose and innovative ecological solutions, give their own judgments regarding the priority of the advantages of the specified criteria. Expert judgments are processed according to the formal procedure of the MAI, which is implemented on a computer, and is the basis for decision-making when choosing the innovative ecological solutions in specific conditions. The criteria hierarchical structure of innovative ecological solutions is represented by a sequence of actions that include the following stages: development of elements of a methodical approach; verification of the consistency of the proposed hierarchical structure for determining priority technologies based on the input data of several objects of settlements; obtaining data on the priority of innovative ecological solutions for implementation on these objects. The advantages of the proposed methodical approach should include the possibility to link to a single algorithm for the justification of the required decision data that differ both in their content and in the form of presentation. Implementation of complex support systems for making innovative decisions in nature protection activities will increase the complexity and effectiveness of decisions to ensure environmental safety.